2014
DOI: 10.1007/978-3-319-04852-9_4
|View full text |Cite
|
Sign up to set email alerts
|

Broadcast Steganography

Abstract: We initiate the study of broadcast steganography (BS), an extension of steganography to the multi-recipient setting. BS enables a sender to communicate covertly with a dynamically designated set of receivers, so that the recipients recover the original content, while unauthorized users and outsiders remain unaware of the covert communication. One of our main technical contributions is the introduction of a new variant of anonymous broadcast encryption that we term outsider-anonymous broadcast encryption with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…They showed that an atomic private broadcast encryption scheme with fully anonymous must have a ciphertext size of Ω(n · k), where n is the number of broadcast set and k is the security parameter. Recently, Fazio, Nicolosi and Perera [13] studied the broadcast steganography and introduced a new construction called outsider-anonymous broadcast encryption with pseudorandom ciphertexts, which achieves sublinear ciphertext size and is secure without random oracles.…”
Section: Related Workmentioning
confidence: 99%
“…They showed that an atomic private broadcast encryption scheme with fully anonymous must have a ciphertext size of Ω(n · k), where n is the number of broadcast set and k is the security parameter. Recently, Fazio, Nicolosi and Perera [13] studied the broadcast steganography and introduced a new construction called outsider-anonymous broadcast encryption with pseudorandom ciphertexts, which achieves sublinear ciphertext size and is secure without random oracles.…”
Section: Related Workmentioning
confidence: 99%
“…An example opposite to that mentioned in [10] is when one sender shares information over a steganographic channel with multiple recipients. This approach was named Broadcast Steganography and presented in [11]. In [11] the authors additionally used encryption to make the hidden message readable only to the authenticated users.…”
Section: • Knowledge Management Use -When Individual Unitsmentioning
confidence: 99%
“…Hopper [21] posed as a challenging open problem to show the (non)existence of a universal SS-CCA-secure stegosystem. Since more than a decade, public key steganography has been used as a tool in different contexts (e. g. broadcast steganography [17] and private computation [9,11]), but this fundamental question remained open.…”
Section: Introductionmentioning
confidence: 99%
“…This strengthens the need for universal stegosystems, as even tiny approximation errors of the channel distribution may lead to huge changes with regard to the security of the system. Fazio, Nicolosi and Perera [17] extended public-key steganography to the multi-recipient setting, where a single sender communicates with a dynamically set of receivers. Their system is designed such that no outside party and no unauthorized user is able to detect the presence of these broadcast communication.…”
Section: Introductionmentioning
confidence: 99%